Cloning, expression, purification, crystallization and preliminary X-ray diffraction analysis of N-acetylmannosamine kinase from methicillin-resistant Staphylococcus aureus - North, Rachel A. (International Union of Crystallography, 2014)

(untitled)
N-Acetylmannosamine kinase (EC 2.7.1.60) is involved in the catabolism of sialic acid for many bacterial pathogens implicated in human disease such as Escherichia coli, Staphylococcus aureus, Vibrio cholerae and V. vulnificus. Interestingly, some human commensals and bacterial pathogens can scavenge sialic acids from their surrounding environment and degrade them as a source of carbon, nitrogen and energy. This process requires a cluster of genes known as the ‘Nan-Nag cluster’, which have proven to be essential for S. aureus growth on sialic acids, suggesting that the pathway is a viable antimicrobial drug target. The enzyme N-acetylmannosamine kinase is involved in the catabolism of sialic acid, transferring a phosphate group from adenosine-5′-triphosphate to the C6 position of N-acetylmannosamine to generate N-acetylmannosamine-6-phosphate. The gene was cloned into an appropriate expression vector; recombinant protein was expressed in E. coli BL21 (DE3) cells and purified via anion-exchange chromatography, hydrophobic interaction chromatography and size-exclusion chromatography. Purified N-acetylmannosamine kinase was screened for crystallization. The best crystal diffracted to a resolution of beyond 2.6 Å in space group P2. Understanding the structural nature of this enzyme from methicillin-resistant S. aureus will provide insights necessary for the development of future antimicrobials.